Legal And Ethical Aspects Of Medicine In Handling The Effects Of Postoperative Anesthesia: Protection Of Patients' Rights And Physician Responsibilities - Muliadi; Fauzan (International Journal of Society and Law, 2024)
The handling of postoperative anesthesia requires special attention to legal and medical ethical aspects, as it involves the patient's right to safe treatment and the doctor's responsibility in providing services according to professional standards. The importance of legal protection and the application of medical ethics is becoming increasingly relevant given the potential complications of anesthesia that can affect the patient's quality of life. This article highlights two main areas, namely the protection of patient rights, such as the right to clear and honest information about the risks of anesthesia, as well as the responsibilities of doctors, including the obligation to ensure patient recovery and avoid medical negligence. This study uses a qualitative method with a juridical-normative approach. Data were obtained through analysis of health law literature, principles of medical ethics, and review of legal cases related to anesthesia malpractice. This approach provides systematic insight into the relationship between legal regulation and ethical principles in medical practice. The results of the study show that negligence in providing adequate information to patients regarding the effects of anesthesia can trigger legal conflicts, such as malpractice lawsuits. In addition, doctors' non-compliance with medical ethical principles, such as nonmaleficence (not harming patients), can damage patient trust and the reputation of the medical profession. In conclusion, the integration between legal protection and the proper application of medical ethics is key to improving the quality of postoperative care, protecting patient rights, and ensuring that doctors' responsibilities are optimally fulfilled.